Thrombotic microangiopathy after kidney transplantion - Mohammad Sami Tahseen; Safa Ezzeddin Nouruldin (Advanced Medical Journal)
Background and objectives: Thrombotic microangiopathy after kidney transplantation is rare but serious complication. The purpose of this study is to describe the cases of thrombotic microangiopathy after kidney transplantation.